2006
DOI: 10.1090/s1061-0022-06-00894-6
|View full text |Cite
|
Sign up to set email alerts
|

A recursion formula for the correlation functions of an inhomogeneous XXX model

Abstract: Abstract.A new recursion formula is presented for the correlation functions of the integrable spin 1/2 XXX chain with inhomogeneity. It links the correlators involving n consecutive lattice sites to those with n − 1 and n − 2 sites. In a series of papers by V. Korepin and two of the present authors, it was discovered that the correlators have a certain specific structure as functions of the inhomogeneity parameters. The formula mentioned above makes it possible to prove this structure directly, as well as to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
88
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 24 publications
0
88
0
1
Order By: Relevance
“…As far as two-point correlation functions of the spin-1/2 chain are concerned, enormous progress has been made in the last decade to obtain exact expressions from Bethe Ansatz [11,12,13] for short distances [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28] and from field-theory for both the amplitudes and the exponents of the leading terms in the asymptotic limit [29,30,31,32]. These results are not restricted to the isotropic point, but cover the critical anisotropic regime as well,…”
Section: Introductionmentioning
confidence: 99%
“…As far as two-point correlation functions of the spin-1/2 chain are concerned, enormous progress has been made in the last decade to obtain exact expressions from Bethe Ansatz [11,12,13] for short distances [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28] and from field-theory for both the amplitudes and the exponents of the leading terms in the asymptotic limit [29,30,31,32]. These results are not restricted to the isotropic point, but cover the critical anisotropic regime as well,…”
Section: Introductionmentioning
confidence: 99%
“…It is desirable that this algebraic method will be generalized to the case with ∆ = 1. Actually, Boos, Jimbo, Miwa, Smirnov and Takeyama have derived an exponential formula for the density matrix elements of XXZ model, which does not contain multiple integrals [27,28,29,30,31]. It, however, seems still hard to evaluate the formula for general density matrix elements.…”
Section: Introductionmentioning
confidence: 99%
“…1. The finding of [4] is striking, a two-point nearest neighbor function !ðx 1 ; x 2 Þ : ¼ 6 tr D 2 ðx 1 ; x 2 ÞS z 1 S z 2 and a set of ''structure constants'' f n;I;J determine the density matrix D n for arbitrary n…”
mentioning
confidence: 97%
“…The recent progress is due to several different but related methods, like the representation theory of quantum algebras, the algebraic Bethe ansatz, or the advent of new functional equations, which first of all led to the derivation of multiple integral representations [2] for the elements of the density matrix. In a series of works [3,4] it was then shown that the correlation functions of an inhomogeneous version of the model can be represented by algebraic expressions of a single function of two variables.…”
mentioning
confidence: 99%
See 1 more Smart Citation